Mononuclear manganese complexes as hydrogen evolving catalysts - Kaim, Vishakha; Joshi, Meenakshi; Stein, Matthias; Kaur-Ghumaan, Sandeep (Frontiers in Chemistry, 2022)
Molecular hydrogen (H2) is one of the pillars of future non-fossil energy supply. In the quest for alternative, non-precious metal catalysts for hydrogen generation to replace platinum, biological systems such as the enzyme hydrogenase serve as a blueprint. By taking inspiration from the bio-system, mostly nickel- or iron-based catalysts were explored so far. Manganese is a known oxygen-reducing catalyst but has received much less attention for its ability to reduce protons in acidic media. Here, the synthesis, characterization, and reaction mechanisms of a series of four mono-nuclear Mn(I) complexes in terms of their catalytic performance are reported. The effect of the variation of equatorial and axial ligands in their first and second coordination spheres was assessed pertaining to their control of the turnover frequencies and overpotentials. All four complexes show reactivity and reduce protons in acidic media to release molecular hydrogen H2. Quantum chemical studies were able to assign and interpret spectral characterizations from UV–Vis and electrochemistry and rationalize the reaction mechanism. Two feasible reaction mechanisms of electrochemical (E) and protonation (C) steps were compared. Quantum chemical studies can assign peaks in the cyclic voltammetry to structural changes of the complex during the reaction. The first one-electron reduction is essential to generate an open ligand-based site for protonation. The distorted octahedral Mn complexes possess an inverted second one-electron redox potential which is a pre-requisite for a swift and facile release of molecular hydrogen. This series on manganese catalysts extends the range of elements of the periodic table which are able to catalyze the hydrogen evolution reaction and will be explored further.